(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
Hypertension is an elevation of systolic blood pressure (SBP) ≥140 mm Hg, or a diastolic blood pressure (DBP) ≥90 mm Hg, or using antihypertensive drugs. Arterial hypertension causes high morbidity and mortality because its harmful impact on many systems, especially the cardiovascular system. Despite good control of their blood pressure, young patients with non-complicated hypertension are usually presented with exercise intolerance which necessitate the search for possible causes. Aim: The present study is targeted to discover possible subtle systolic dysfunction and its correlation with exercise capacity among young age patients with chronic non complicated hypertension as well as to assign the main factors affecting exercise capacity in those patients. Methods: A total of 80 young age participants involved in this study. They are grouped as a group I (control subjects) , n= 40 (female: 17, male: 23) and group II (hypertensive patients), n= 40 (male: 27, female: 13) with different BMI levels. Group II further subdivided into group A (exercise capacity > 7 MET) and B (exercise capacity≤7 MET). Strain analysis was performed using propriety software on the echocardiograph. TDI and PWD are used to measure E/e, and PCWP. All participants are subjected to treadmill test using Bruce protocol in order to obtain exercise capacity and to exclude IHD. Results: Compared to normal subjects, non-complicated hypertensive patients have significantly reduced GLS (P value: 0.00) and increased PSI (P value: 0.00) as well as a significant increase in E/e, (P value: 0.00), PCWP (P value: 0.00) and a significant reduction in exercise capacity (P value: 0.00). In hypertensive patients with exercise capacity ≤7 MET versus those with exercise capacity >7 MET, there is no statistical difference between the average GLS (P value:0.6), average PSI (P value: 0.07) while significant elevation of E/e, (P value: 0.01) and PCWP (P value: 0.01) are observed in hypertensive patients with lower exercise capacity. Conclusion: Though significant changes in GLS, PSI and lower exercise capacity are evident in hypertensive patients in relation to healthy control subjects, Low exercise capacity in those patients is related to significant diastolic changes rather than subclinical systolic dysfunction.